INDEKS PENCEMARAN PERAIRAN LAUT: STUDI KASUS PERAIRAN LABUHAN SANGORO, TELUK SALEH KABUPATEN SUMBAWA - Baiq Hilda Astriana; Aryan Perdana Putra; Baiq Fadila Arlina (Universitas Mataram, 2024)
Saleh Bay is a region in West Nusa Tenggara Province known for its significant marine resource potential, on which most coastal communities rely for their livelihoods. One of the most important activities for these communities is seaweed cultivation. Besides supporting the local economy, this activity has also made West Nusa Tenggara one of the largest seaweed producers in Indonesia. However, declining water quality has led to a decrease in seaweed production. This issue has occurred in certain areas of Saleh Bay, such as Labuhan Sangoro. This decline commonly happens during specific seasons (the rainy season) and as a result of ice-ice disease. Monitoring water conditions is essential to provide a reference for seaweed farmers on the water quality in their cultivation areas. This study was conducted in February 2024, coinciding with the rainy season. Water sampling was carried out using purposive sampling at six stations, which were cultivation locations (sampling stations from the previous year). Measurements of seawater chemical and physical parameters were conducted in situ and at the Lombok Marine Aquaculture Center Laboratory. The data obtained from these measurements were then analyzed descriptively using the Pollution Index method based on the Indonesian Minister of Environment’s Decree No. 115 of 2003. The Pollution Index evaluation indicated that in February 2024, the waters of Labuhan Sangoro remained at a moderate pollution level (PI=6.1), with some stations showing parameter values exceeding the quality standards.